THE IMPACT OF TEACHER'S POSITIVE ATTITUDE AND ENTHUSIASM ON TEACHING EFL - Ratna Dwiyaning Raharjanti (Faculty of Education and Teachers Training, 2019)
AbstractThis paper discusses how students’ perspective about teacher’s positive attitude and enthusiasm on teaching English as Foreign Language. The success of the lesson depends on the teacher’s way to teach.. When a difficulty is found on teaching that makes the students feel not enthusiastic, applying positive attitude and enthusiasm will be the solution so that they are encouraged to learn. The purpose of this study is to prove that teacher’s positive attitude gives big influence on a learning process. This paper uses qualitative research which involving the author’s arguments. The author creates a questionnaire to observe this problem and the result shows that most students need teacher’s positive attitude and enthusiasm in supporting their study. Therefore, teacher should consider his attitude while they are teaching.